Evidence that herpes simplex virus DNA is transcribed by cellular RNA polymerase B. - Costanzo, F (1977)
In herpes simplex virus type 1 (HSV-1)-infected HEp-2 cells, amanitin added before or at various times after infection always reduced viral multiplication. Also, the three waves of transcription of HSV-1 DNA, which led to the synthesis of alpha, beta-, and gamma-polypeptides, were all sensitive to amanitin in HEp-2 cells, and the amanitin-sensitive RNA polymerase activities of isolated nuclei were equally sensitive to the inhibitor before and during the infection. On the contrary, HSV-1 DNA transcription was totally unaffected by amanitin in AR1/9-5B cells, a mutant subline of CHO cells that possesses an amanitin-resistant RNA polymerase B. Together, these results strongly suggest that HSV-1 DNA utilizes for its transcription a polymerase undistinguishable from host cell RNA polymerase B with respect to its sensitivity to amanitin.